Effect of ITO surface properties on SAM modification: A review toward biosensor application. Issue 1 (31st December 2016) - Khan, Md. Zaved Hossain
Abstract: The aim of this review is to discuss the effect of physical and chemical properties of Indium tin oxide (ITO) thin film on its self-assembled monolayer (SAM) modification, as well as device performance toward biosensor applications. The emphasis is on surface morphology studies of the thin films in order to provide connecting points between surface properties with the broader field of material science of ITO. The morphology of SAM film deposited on it directly affects by the properties of these prepared ITO film. Thus, it is a topic of interest to study the influence of physiochemical properties of this film on device fabrication and applications as biosensor platform.